Adjuvant effect of Bacillus firmus on the expression of cytokines and toll-like receptors in mouse nasopharynx-associated lymphoid tissue (NALT) after intranasal immunization with inactivated influenza virus type A - Zanvit, Peter; Tichopád, Aleš; Havlíčková, Martina; Novotná, Olga; Jirkovská, Marie; Kološtová, Katarína; Cechová, Dana; Julák, Jaroslav; Sterzl, Ivan; Prokešová, Ludmila (Immunology letters, 2010)
Due to the persisting threat of development of new highly pathogenic influenza A subtypes, a mucosal vaccination which would induce a potent and cross-protective reaction is desirable. We succeeded in mucosal immunization of mice with an inactivated influenza A virus by using delipidated Bacillus firmus (DBF) as adjuvant. The mechanism of adjuvant effect was followed in NALT by comparing the response after intranasal immunization by inactivated influenza virus type A (H1N1) alone, adjuvant alone (DBF), or by a mixture of virus+DBF. Expression of selected gene groups was tested via qPCR at 7 different time-points: cytokines (IL-2, IFN-γ, IL-4, IL-6, and IL-10), type I interferons (IFN-α4, IFN-α11, IFN-α12, and IFN-β), toll-like receptors (TLR2, TLR3, TLR7, and TLR9), iNOS and CCR7. Intranasally administered DBF and the mixture of virus+DBF induced an elevated expression of IFN-γ, IL-6 and IL-10 cytokines, type I interferons, iNOS, and pDC markers in NALT. Multimarker qPCR data was analyzed by relative quantification and by principal component analysis. DBF has been shown to be a very efficient adjuvant for the stimulation of innate immunity after IN immunization. DBF accelerated, increased, and prolonged the antiviral response.
Keywords: Toll-Like Receptor 3; synergismus léků; toll-like receptory; Adjuvants, Immunologic; zvířata; interleukin-10; lymfoidní tkáň; interferon typ I; Cytokines; Mice, Inbred BALB C; Principal Component Analysis; virus chřipky A, podtyp H1N1; cytokiny; Reverse Transcriptase Polymerase Chain Reaction; myši; časové faktory; Mice; Bacillus; Toll-Like Receptor 2; Toll-Like Receptors; Gene Expression; Interleukin-2; polymerázová řetězová reakce s reverzní transkripcí; toll-like receptor 7; Nasopharynx; analýza hlavních komponent; Lymphoid Tissue; Toll-Like Receptor 7; Influenza Vaccines; aplikace intranazální; exprese genu; myši inbrední BALB C; adjuvancia imunologická; Immunization; Administration, Intranasal; Animals; vakcíny proti chřipce; nazofarynx; Time Factors; interleukin-2; toll-like receptor 3; Toll-Like Receptor 9; Interferon Type I; Influenza A Virus, H1N1 Subtype; Membrane Glycoproteins; Interleukin-10; toll-like receptor 9; imunizace; Drug Synergism; toll-like receptor 2; membránové glykoproteiny